Determinación del valor de los espacios públicos abiertos para el mejoramiento de la gestión urbana en la ciudad de Riobamba - Granda Castillo, Mariana de Jesús (2019)
Open public spaces (OPS) are the key to sustainable urban development within cities, being considered as the root of urbanism since in addition to its physical functions incorporate economic, social and environmental factors. This research determines the quantity, quality and use of Riobamba's open public spaces allowing them to know their current situation. The study is carried out by evaluating each OPS identified, through a conceptualization and classification based on the particularity of the city. Through the theoretical framework according to global, national and local literature, the open public spaces to be studied are determined. Using the KoBoToolbox platform assesses the current status of 143 areas through a digital survey with interviews, photographs, audio and observation, collecting data in the categories spatial location, accessibility, use, comfort, physical character, green area, safety and users. This leads to a diagnosis of open public spaces at the city level, resulting in a regular average about its quality, which is evident in situational, evaluative and conclusive mappings, which in the future will serve for the improvement of the urban management of Riobamba. KEY WORDS: Open public spaces, evaluation, function